Investigating the Co-integration between Exports and Female Employment: A Case Study of Pakistan (International Journal of Scientific Research and Management (IJSRM), 2016)
Female’s employment play fundamental role in the economic development. Exports play essential role for boosting the female employment. Exports and female employment have been improved over the time that become a good source of growth in Pakistan. The study used time series data from the period 1985 to 2013. Unit root tests are used to explore the stationarity of time series data. The present study investigates the Co-integration among economic determinants by employing Johansen’s Co-integration test and Error Correction Model. Empirical findings of the study indicate that export, government spending, education spending by the government and value addition in industries are positively associated with female employment in Pakistan. This study recommended that the government should enhance spending on education that promote female employment. Moreover, government should take suitable actions to execute export oriented policy. It is the need of time for development of any developing nation, value addition in industries requisite to be supported by the government to enhance the female employment